Effects of Altitudinal Gradient on Physicochemical and Rheological Potential of Quinoa Cultivars - Garcia-Parra, Miguel Ángel; Roa-Acosta, Diego Fernando; Bravo-Gomez, Jesús Eduardo; Hernández-Criado, Juan Carlos; Villada-Castillo, Héctor Samuel (Frontiers in Sustainable Food Systems, 2022)
The protein, carbohydrate, and fat characteristics of quinoa grains reflect in their techno-functional potential. This aspect has been little studied in quinoa, while some physicochemical and rheological characteristics have been generalized for all cultivars under all primary production conditions. The aim of this research is to determine the agro-industrial potential of different quinoa cultivars evaluated under different environments through physicochemical and rheological responses. This study has a factorial design with a first level corresponding to cultivars and a second level to production zones. The results showed that the cultivars present high compositional variability. It was also found that the altitudinal gradient changes protein and starch composition, protein secondary structure, and starch structural conformation. In addition, significant variations were found in viscosity, breakdown, and dispersion setback for all treatments. However, there were no differences between treatments before heating/cooling and after heat treatment.